THE IMPACT OF DIGITAL PROMOTION AND THE QUALITY OF GO-FOOD APPLICATION SERVICES ON PURCHASE DECISIONS - Bunga Aditi; Rian Ardianto; Fachrurazi Fachrurazi (SEAN Institute, 2023)
The purpose of this study is to find out and analyze the effect of Go-Food services as a media promotion on food purchasing decisions in the city of Bandung. To find out and analyze the effect of Go-Food Service Quality on food purchasing decisions in the city of Bandung. The data in this study were tested using validity and reliability tests, multiple regression analysis, coefficient of determination, f test, and t test to test the hypothesis proposed by the researcher. Based on the results of simultaneous research on digital promotion and go-food service quality, they have a positive and significant effect on purchasing decisions with a significant value of 0.015 <0.05, this test shows that the hypothesis is accepted. The digital promotion variable has a positive and significant effect on the purchase decision variable. Furthermore, the service quality variable has a positive and significant effect on the purchasing decision variable. Purchase decisions at food outlets are influenced by digital promotions and the quality of go-food services, this is evidenced by the R square value of 37.9% while the rest are influenced by other factors.